Conditions for Increasing the Effectiveness of Education in a Modular Educational System - Nasimova, Z. I.; Nasimova, Z. I. (European Journal of Life Safety and Stability (2660-9630), 2022)
Module Program, as a training manual that teaches independent reading at the time of reading the block of educational material included in the module of study for the student the effectiveness of training increases if it is given for permanent use.